2020
DOI: 10.21608/svuijas.2020.32781.1013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slow release fertilizers on growth and fruiting of Khalas date palm

Abstract: The current investigation was carried out during 2018 and 2019 seasons to study the effect of some fertilizer practices on yield, fruit quality and some mineral content of Khalas date palm grown in a private farm, Luxor Governorate, Egypt. Results showed that significant improved due to use slow release fertilizers as well as comparing total soluble fertilizers in terms of vegetative growth and nutritional status yield, bunch weight and fruit quality during both seasons. Using 600 g of N and 300 g of K via slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…An increase in K content in leaves with the application of K fertilizer was evident, as these fertilizers provide more available K content in soil for the uptake of K via plant roots. Results are in line with findings reported in earlier studies (Srivastava and Singh, 2006;El-Salhy et al, 2010;Desai et al, 2014;Soti et al, 2015;and Salem and Ali, 2020), who also confirmed that K fertilizer application improved K contents in different plant parts, particularly in the shoot. Enhanced K content in leaves with K fertilizer application was due to more K uptake by plant roots that can denote more K availability in the medium.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An increase in K content in leaves with the application of K fertilizer was evident, as these fertilizers provide more available K content in soil for the uptake of K via plant roots. Results are in line with findings reported in earlier studies (Srivastava and Singh, 2006;El-Salhy et al, 2010;Desai et al, 2014;Soti et al, 2015;and Salem and Ali, 2020), who also confirmed that K fertilizer application improved K contents in different plant parts, particularly in the shoot. Enhanced K content in leaves with K fertilizer application was due to more K uptake by plant roots that can denote more K availability in the medium.…”
Section: Discussionsupporting
confidence: 93%
“…Enhanced K content in leaves with K fertilizer application was due to more K uptake by plant roots that can denote more K availability in the medium. Study findings agree with results reported in earlier studies (Ashraf et al, 2010;Soti et al, 2015;Salem and Ali, 2020) and proved that K fertilizer application improved soil K contents.…”
Section: Discussionsupporting
confidence: 93%
“…Potassium solubilizing bacteria (KSB) dissolve K from dissolve K-bearing minerals such as mica, illite, and orthoclase, by secreting organic acids, which either directly dissolved rock potassium or chelated silicon ions to bring potassium into the solution. (Sindhu et al 2010 The promotive effect of different potassium fertilizer sources on fruiting of date palm trees were emphasized by (Bamiftah, 2000;Soliman and Osman, 2003;Ahmed, 2008;Osman, 2010;Elamin et al, 2017;El-Salhy et al, 2017;Omer et al, 2018;Shalan andEl-Boray, 2019 andSalem andAli, 2020). They concluded that using different forms of potassium fertilization had a positive effect on yield and fruit quality of date palm cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Using slow release fertilizers appears to be effective in improving the growth and fruiting of most fruit trees. These findings might be due to continuous adjustment of nutrients during all stages of growth and fruit development (Miller et al, 1990;Furuya, 1995;Fageria andBaligar, 2005 andSalem andAli, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation